Degradation of the Mitchell River fluvial megafan by alluvial gully erosion increased by post-European land use change, Queensland, Australia - Shellberg, J.G.; Spencer, J.; Brooks, A.P.; Pietsch, T.J. (Geomorphology (Amsterdam, Netherlands), 2016)
Along low gradient rivers in northern Australia, there is widespread gully erosion into unconfined alluvial deposits of active and inactive floodplains. On the Mitchell River fluvial megafan in northern Queensland, river incision and fan-head trenching into Pleistocene and Holocene megafan units with sodic soils created the potential energy for a secondary cycle of erosion. In this study, rates of alluvial gully erosion into incipiently-unstable channel banks and/or pre-existing floodplain features were quantified to assess the influence of land use change following European settlement. Alluvial gully scarp retreat rates were quantified at 18 sites across the megafan using recent GPS surveys and historic air photos, demonstrating rapid increases in gully area of 1.2 to 10 times their 1949 values. Extrapolation of gully area growth trends backward in time suggested that the current widespread phase of gullying initiated between 1880 and 1950, which is post-European settlement. This is supported by young optically stimulated luminescence (OSL) dates of gully inset-floodplain deposits, LiDAR terrain analysis, historic explorer accounts of earlier gully types, and archival records of cattle numbers and land management. It is deduced that intense cattle grazing and associated disturbance concentrated in the riparian zones during the dry season promoted gully erosion in the wet season along steep banks, adjacent floodplain hollows and precursor gullies. This is a result of reduced native grass cover, increased physical disturbance of soils, and the concentration of water runoff along cattle tracks, in addition to fire regime modifications, episodic drought, and the establishment of exotic weed and grass species. Geomorphic processes operating over geologic time across the fluvial megafan predisposed the landscape to being pushed by land used change across an intrinsically close geomorphic threshold towards instability. The evolution of these alluvial gullies is discussed in terms of their initiation, development, future growth, and stabilisation, and the numerous natural and anthropogenic factors influencing their erosion. •Alluvial gully erosion into floodplains is widespread across northern Australia.•River incision into megafans creates the potential energy for new erosion cycles.•Air photo and OSL data demonstrate rapid gully expansion post-European settlement.•Cattle grazing increases erosion into incipiently-unstable floodplain features.•Natural and anthropogenic factors influence geomorphic thresholds and gully evolution.